Strawberry Generation: When Strawberry Parenting and Teaching Weaken Students’ Mathematical Resilience - Jayanti, Tety; Kawuryan, Sekar Purbarini (FKIP Universitas Lampung, 2025)
Abstract: Strawberry Generation: When Strawberry Parenting and Teaching Weaken Students' Mathematical Resilience. Objectives: This study aims to investigate the impact of the